The Art of Leadership Qualities in Human Governance of Human Capital - Siti Sarawati Johar; Linayati Lestari; Nesreen Awada (Journal of Management Practices, Humanities and Social Sciences, 2020)
The purpose of this study is to explore and discusses about the leadership qualities in human governance of human capital. This study also investigated the characteristics of leadership in human governance that have a significant impact on the human capital. This study is qualitative in nature such that a comprehensive review of existing literature was conducted. This conceptual paper discussed some of the leadership qualities needed in the formation of strong human governance of human capital. These leadership qualities include a positive dimension of values that should be interpreted explicitly and implicitly. The findings of current study highlight that the qualities of a leader are not only based on the language of his words, but also the language of his body which must conform to what is implied in his mind and soul, which is reflected in his behaviour. Moreover, the dark side of a leader will only change the landscape of the organization because there will be a pattern of reckless compliance with followers who dispel their ethics and manners. Therefore, a leader needs to put the goodness side of themselves as a highlight based on leadership to ensure that everything is in line with universal values and society demands.